Post-fledging survival of Tengmalm’s owl offspring in boreal forests: Interactive effects of varying dynamics of main prey and habitat composition - Kouba, Marek; Bartoš, Luděk; Tulis, Filip; Ševčík, Michal; Sovadinová, Simona; Bušina, Tomáš; Janouš, Martin; Kouba, Petr; Bartošová, Jitka; Hongisto, Kari; Korpimäki, Erkki (Frontiers in Ecology and Evolution, 2023)
The knowledge about the mortality rate of offspring is crucial for estimating bird population dynamics and conserving species with declining populations. Parents of predatory birds provide food for their offspring during the post-fledging dependency period, which is frequently described as essential due to inexpert flying skills. Using radio telemetry, we studied fledglings’ probability of dying by starvation and predation in Tengmalms’ owls (Aegolius funereus). Nestlings (21 and 39) from 10 and 14 broods in 2019 and 2021, respectively, were equipped with leg-mounted tags and monitored throughout the post-fledging dependency period in west-central Finland. In total, 28 out of 60 fledglings did not survive the post-fledging dependency period (12 died due to starvation, and 16 were predated). The fledglings’ probability of dying by starvation and predation was 3.7 and 2.4 times higher, respectively, in the decreasing (2019) than during the increasing (2021) abundance of main foods (voles), showing that prey availability is essential for survival during the post-fledging dependency period. The probability of starvation increased with augmenting agricultural lands in the home range and increasing precipitation after fledging, which indicated that parent owls avoided hunting in open areas and during rainy nights. The predation rate during the post-fledging dependency period increased with augmenting cover of old-growth forests in the home range. This result suggested that coverage of old-growth forests is nowadays so small in the study area that they act as ecological traps for newly-fledged owlets. The reason is that the main avian enemies of Tengmalm’s owls’ (goshawks and Ural owls) also prefer old-growth forests for breeding and hunting.